Arbuscular Mycorrhizal Fungi Enhance Drought Stress Tolerance by Regulating Osmotic Balance, the Antioxidant System, and the Expression of Drought-Responsive Genes in Vitis vinifera L. - Qiuhong Ye; Hua Wang; Hua Li (Australian Journal of Grape and Wine Research)
Background and Aims. Drought harms the growth and productivity of grapevines; it thus poses a major threat to the development of viticulture in the background of ongoing climate change. Arbuscular mycorrhizal fungi (AMF) can be used to enhance the resistance/tolerance of plants to environmental stress. The effects of AMF on the osmotic regulation, antioxidant substances, and expression of drought-responsive genes in the grapevine Vitis vinifera L. cv. Ecolly were studied. Methods and Results. The experiment was conducted in a greenhouse in a completely randomized block design with four treatments: AMF colonization, well-watered; non-AMF colonization, well-watered; AMF colonization with drought stress; and non-AMF colonization with drought stress. The concentration of sucrose and proline in the leaves was higher in mycorrhizal grapevine than in nonmycorrhizal grapevine under drought stress. The concentration of malonaldehyde, hydrogen peroxide, superoxide anion, and glutathione and the activity of superoxide dismutase and peroxidase activity in leaves were higher in mycorrhizal grapevine than in nonmycorrhizal grapevine under drought conditions. AMF inoculation affected the expression of drought-responsive genes. Mycorrhization upregulated the expression of VvNCED, VvP5CS, VvSIP, VvPIP1;2, and VvTIP2;1 genes under drought stress. Conclusions. AMF could reduce the harm caused by drought stress by regulating osmosis, antioxidant activities, and the expression of key drought-responsive genes and aquaporin genes. Significance of the Study. This work provides insights into the physiological and biochemical activities influenced by AMF on grapevine under drought stress.